Corporate governance: Does the concept work in transition economies? - Andrei Petrovich Kuznecov; Olga Kuznecova (Journal for East European Management Studies, 2003)
The paper evaluates the feasibility of employing mainstream models of corporate governance in the context of transition economies, using Russia as an example. The issue of corporate governance is considered as an element of an institutional crisis characteristic of post-communist countries. It is maintained that the stakeholder approach provides the closest fit to the realities of corporate governance in a country like Russia. – – Dieses Papier untersucht die Möglichkeit der Anwendung von Normalmodellen der Unternehmensführung im Kontext der Volkwirtschaften der Reformländer mit besonderer Bezugnahme auf Rußland. Das Gebiet der Unternehmsführung wird als ein Element der institutionellen Krise in den post-kommunistischen Ländern erachtet. Es wird argumentiert dass der Stakeholder Ansatz am ehesten den Realitäten der Unternehmensführung in Ländern wie Rußland enstpricht.
Keywords: 650; Institutional economics; corporate governance; transition; Russia; post-communism